1-(2-Bromoethyl)-1,4-diazoniabicyclo[2.2.2]octane bromide dihydrogen phosphate–phosphoric acid (1/1) - Xiao, Jing-Mei (International Union of Crystallography, 2010)
In the crystal structure of the title compound, C(8)H(17)BrN(2) (2+)·Br(−)·H(2)PO(4) (−)·H(3)PO(4), the cations, anions and phosphoric acid molecules are linked by O—H⋯O, N—H⋯O and O—H⋯Br hydrogen bonds into layers parallel to (101).